POP-UP BOOK DIGITAL 20.20.20 MEMPENGARUHI PENGETAHUAN PENCEGAHAN SINDROM PENGLIHATAN KOMPUTER PADA SISWA SEKOLAH DASAR (Politeknik Kesehatan Kemenkes Bandung, 2021)
Computer vision syndrome (CVS) can appear in elementary school students as the behavior of using gadgets is not appropriate, the increase in SPK cases occurs during the Covid pandemic caused by prolonged use of gadgets. The American Optometric Association suggests preventing CVS by applying the 20.20.20 method when using gadgets and taking other precautions such as adjusting the length of use, visibility, lighting, sitting position, and others. Therefore, it is necessary for health promotion media for elementary school students to be able to implement CVS prevention by using a digital pop-up book, which describes SPK prevention behavior with an attractive appearance and can be accessed easily. The purpose of this study was to analyze the effect of digital pop-up book media method 20.20.20 on knowledge of preventing computer vision syndrome (SPK) in Cibogo 2 Elementary School students, Cianjur Regency in 2021. This study used pre-experimental with one group pretest-posttest without control. . The sampling technique used non-probability sampling with purposive sampling as many as 69 elementary school students with an increase in knowledge of 51.60%. The normality test used Kolmogrof Smirnov with the results of the data is normally distributed and the Paired T-test to determine the effect with the results of p-value 0.000 < 0.005. The results of the analysis show that the digital pop-up book media method 20.20.20 affects knowledge of preventing computer vision syndrome (CVS) in Cibogo 2 Elementary School students, Cianjur Regency in 2021.